2022
DOI: 10.1002/jemt.24236
|View full text |Cite
|
Sign up to set email alerts
|

Biological features of the pecten oculi of the European wild quail (Coturnix coturnix): Adaptative habits to Northern Egyptian coast with novel vision to its SEM–EDX analysis

Abstract: The present investigation was prepared to give a complete ultrastructural characterization of the pecten oculi of the diurnal European wild Quail to describe their adaptation habits to the Northern Egyptian coast. Our work declares the first endeavor is the elemental analysis using scanning electron microscopy‐energy dispersive X‐ray (SEM–EDX) to show the migration effect on their eye. The intra‐ocular quadrilateral trapezoid black pigmented plicated type pecten oculi were observed on the postero‐inferior wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(25 citation statements)
references
References 46 publications
8
17
0
Order By: Relevance
“…Additionally, the pecteneal apex differs slightly between different species of birds. In this study, the free pecteneal apex was fused with one another, forming a free apical bridge that was directed towards the gelatinous vitreous body and ciliary body, similar to what was seen in a variety of diurnal birds, such as the migratory Garganey, budgerigar, black kite, chicken, white stork, Baladi ducks, common buzzard, seagulls, northern bald ibis, and migratory European wild quail (Abumandour et al, 2021;Abumandour et al, 2022;Alan et al, 2020;Gültiken et al, 2012;Ince et al, 2017;Kiama et al, 1994;Micali et al, 2012;Moselhy & El-Hady, 2019;Onuk, Tutuncu, et al, 2013;Puzzolo et al, 1985;Yilmaz et al, 2021), while the free pecteneal apex…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Additionally, the pecteneal apex differs slightly between different species of birds. In this study, the free pecteneal apex was fused with one another, forming a free apical bridge that was directed towards the gelatinous vitreous body and ciliary body, similar to what was seen in a variety of diurnal birds, such as the migratory Garganey, budgerigar, black kite, chicken, white stork, Baladi ducks, common buzzard, seagulls, northern bald ibis, and migratory European wild quail (Abumandour et al, 2021;Abumandour et al, 2022;Alan et al, 2020;Gültiken et al, 2012;Ince et al, 2017;Kiama et al, 1994;Micali et al, 2012;Moselhy & El-Hady, 2019;Onuk, Tutuncu, et al, 2013;Puzzolo et al, 1985;Yilmaz et al, 2021), while the free pecteneal apex…”
Section: Discussionsupporting
confidence: 73%
“…These coiled surfaces provide a large surface area for efficient nutrient exchange between the blood capillaries and the retina; additionally, this specialized structure helps to maintain the health and functionality of the non-vascular retina by ensuring a constant supply of nutrients. Moreover, high SEM magnification showed that the pecteneal pleat's outer surface is covered by a thin smooth vitreopecteneal limiting membrane separating the pleat's outer surface from the gelatinous vitreous body, similar to that observed in many avian species (Abumandour et al, 2021;Abumandour et al, 2022;Elghoul et al, 2022;Kandyle et al, 2022;Uehara et al, 1996).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations